The Role of Sustainable Supply Chain Practices on the performance of organizations - Mark Alvin Buwembo (Uganda Christian University, 2024)
This study examined the role of sustainable supply chain practices on the operational performance of Coca Cola Beverages in Mbarara. The study was guided by three objectives: to examine the role of sustainable purchasing on operational performance; to assess the role of supplier collaboration on operational performance; and, to assess the role of logistics optimization on operational performance. The respondents of this study included Coca Cola Beverages Mbarara staff. They were selected on their basis of having crucial roles they play in the sustainable supply chain practices and the operational performance in Coca Cola Beverages in Mbarara. A total of 65 respondents formed the sample size of the study. The study employed a cross sectional design and adopted a mixed approach. Questionnaires were used for the purpose of data collection and an interview guide was employed for qualitative data. The response rate was 100% of the targeted sample size. The study found out that role of sustainable purchasing on operational performance is that it enables the company to deliver value adding products to its customers as concurrently helping it provide services of unique quality to its customers by delivering its products on time. The study concluded that supplier collaboration enables the company to create a competitive advantage through sharing information making joint decisions and helps us satisfy customer needs in our operations while assisting the company in its operational inter-organizational relationships. The study also concluded that logistics optimization reduces costs across our supply chain and enhances us meet the growing demand for fast and efficient supply chain operations through lead times and enhancement of customer satisfaction. The study recommends that sustainable purchasing should be further enhanced so that it augurs the operational performance through delivering value added products to its customers by providing services of unique quality and delivery of products on time. The study also recommends that supplier collaboration should be emphasized through sharing information and making joint decisions so as to enable the company to create a competitive advantage while fostering operational inter-organizational relationships. The study further recommends that logistics optimization should be prioritized to enable the company to reduce costs across its supply chain. This will help the company meet the growing demand for fast and efficient supply chain operations. This can be done through ensuring lead times for enhancement of customer satisfaction.